Effect of the vinasse in the cultivation soil of Saccharum officinarum L. “sugar cane” (SCIÉNDO INGENIUM, 2022)
The research aims to determine the effect of vinasse on the soil of Saccharum Officinarum L. "sugar cane" crops. The sample used for the tests was obtained from the Distillery of the Casa Grande SAA company and the application was carried out together with the irrigation water by means of a cistern tank. It was carried out in 5 blocks with 3 repetitions, each block with the dose T1: Control, T2: 30 m3.ha-1, T3: 60 m3.ha-1, T4: 110 m3.ha-1, T5: 220 m3. ha-1, and the samples were analyzed at 15, 30, 60, 90, 120 and 270 days after applying the vinasse. It was determined that there is a significant difference in the Electrical Conductivity (EC) and in the concentration of exchangeable and available potassium, while the pH, the Cation Exchange Capacity, Ca, Mg, Na, N, P, organic matter, carbonates and micronutrients like B and Cu, there is no significant difference. It is concluded that the application of vinasse in sugarcane crops has a significant effect on K, which is important in crop growth.
Keywords: Vinasse; ground; sugar cane; irrigation; chemical parameters